THE RELATIONSHIP OF THE ROLE OF MOTHER IN MAINTAINING ORAL HYGIENE WITH THE EVENT OF CARIES RAMPANT IN ONE ROOF KINDERGARTEN CHILDREN, ACEH BESAR DISTRICT IN 2019 - Cut Ratna Keumala; Sisca Mardelita (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Poor dental health for children such as rampant caries which can cause pain and difficulty chewing will cause disruption in food intake which in turn will affect the child's nutritional status so that the child's growth and development is disrupted. The role of a mother in children's dental health as a motivator, educator and facilitator. This study aims to determine the relationship between the role of mothers in maintaining dental and oral hygiene with the incidence of rampant caries in One Roof Kindergarten children, Aceh Besar District. Methods: This study is an analytic study with a cross sectional approach, the sample in this study used a saturated sampling technique, namely 35 mothers and 35 children. by examining the rampant caries in children and interviewing the mother using a questionnaire. The results were tested statistically using the SPSS program with the chi-square test (α = 0.05). Results: There was a significant relationship between the role of mothers in maintaining dental and oral hygiene with the incidence of caries rampant among children in One Roof Kindergarten, Aceh Besar district (p value = 0.027). Conclusion: The role of mothers in maintaining dental and oral hygiene has a significant relationship with the incidence of caries rampant in One Roof Kindergarten children in Aceh Besar district in 2019.